Evaluation of a computerised polysomnography system. - Biernacka, H (1993)
BACKGROUND: Manual analysis of sleep, breathing, and oxygenation records is the "gold standard" for diagnosing sleep abnormalities but is time consuming and cumbersome. The accuracy and cost of a computerised sleep analysis system have therefore been investigated. METHODS: Manual and computerised (CNS Sleep Lab) scores from 43 consecutive clinical sleep studies were prospectively compared for accuracy and the time and costs were recorded. RESULTS: There were good correlations and no systematic differences between manual and computer scoring for total sleep time, sleep onset latency, and duration of REM sleep. There was a small but clinically insignificant systematic difference in breathing pattern analysis, the number of hypopnoeas/hour being lower with manual than with computer scoring (13 (SE 3) v 15 (SE 3)/hour). There was no difference between computer and manual scoring of the frequency of apnoeas, so the frequency of apnoeas + hypopnoeas was clinically insignificantly higher with computer scoring with a highly significant correlation between the two techniques. The time taken to perform the analyses was not different between the two methods (manual 83 (SE 8) v computer 86 (SE 8) minutes). The computer system was six times more expensive than the manual system and annual running costs, including full maintenance contract and 15% depreciation, were twice as great. CONCLUSION: The CNS Sleep Lab is sufficiently accurate for use in clinical sleep studies but is significantly more expensive and does not save technician time.